Network analysis of the relationships between problematic smartphone use and anxiety, and depression in a sample of Chinese college students - Guo, Zhihua; Yang, Tianqi; Qiu, Rui; Qiu, Huake; Ren, Lei; Liu, Xufeng; Han, Zheyi; Zhu, Xia (Frontiers in Psychiatry, 2023)
Background: Problematic smartphone use (PSU) is associated with both anxiety and depression. However, the relationships between components of PSU and symptoms of anxiety or depression have not been investigated. Hence, the aim of this study was to closely examine the relationships between PSU and anxiety and depression to identify the pathological mechanisms underpinning those relationships. A second aim was to identify important bridge nodes to identify potential targets for intervention. Methods: Symptom-level network structures of PSU and anxiety, and PSU and depression were constructed to investigate the connections between the variables and evaluate the bridge expected influence (BEI) of each node. Network analysis using data from 325 Chinese healthy college students was performed. Results: Five strongest edges appeared within the communities in both the PSU-anxiety and PSU-depression networks. The “Withdrawal” component had more connections with symptoms of anxiety or depression than any other PSU node. In particular, the edges between “Withdrawal” and “Restlessness” and between “Withdrawal” and “Concentration difficulties” were the strongest cross-community edges in the PSU-anxiety network and PSU-depression network, respectively. Furthermore, “Withdrawal” had the highest BEI in the PSU community in both networks. Conclusions: These findings provide preliminary evidence of the pathological pathways linking PSU with anxiety and depression, with “Withdrawal” linking PSU with both anxiety and depression. Hence, ‘‘Withdrawal’’ may be a potential target for preventing and intervening in cases of anxiety or depression.